2016
DOI: 10.1002/eji.201546163
|View full text |Cite
|
Sign up to set email alerts
|

NKp46‐mediated Dicer1 inactivation results in defective NK‐cell differentiation and effector functions in mice

Abstract: MicroRNAs control developmental pathways and effector functions in immune cells. Previous studies have studied the role of microRNAs in natural killer (NK) cells. However, the mouse models of microRNA depletion used were nonNK-specific and only partially depleting, hampering the interpretation of the data obtained. To clarify the role of microRNAs in murine NK cells, we deleted the RNase III enzyme Dicer1 in NKp46-expressing cells. We observed a drastic decrease in several microRNAs specifically in NK cells. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…Apart from the regulation of gene expression on the transcriptional level, another epigenetic mechanism is required for the proper development of ILC1s and the adequate maturation of NK cells. Available data implicate small noncoding RNA molecules (221)(222)(223)(224)(225)(226), such as microRNAs (miRs), to regulate posttranscriptional gene expression by binding to the 3 ′ untranslated region (UTR) of mRNAs and inducing either suppression or mRNA translation or its degradation (227). Deletion of the RNase III enzyme Dicer-1, an enzyme required for the generation of single-stranded 20-25 bp long non-coding RNA molecules, in NKp46-expressing cells revealed the role of miRs in murine NK cells and ILC1s (223).…”
Section: Epigenetic and Microrna-mediated Regulation Of Nk Cell And Imentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the regulation of gene expression on the transcriptional level, another epigenetic mechanism is required for the proper development of ILC1s and the adequate maturation of NK cells. Available data implicate small noncoding RNA molecules (221)(222)(223)(224)(225)(226), such as microRNAs (miRs), to regulate posttranscriptional gene expression by binding to the 3 ′ untranslated region (UTR) of mRNAs and inducing either suppression or mRNA translation or its degradation (227). Deletion of the RNase III enzyme Dicer-1, an enzyme required for the generation of single-stranded 20-25 bp long non-coding RNA molecules, in NKp46-expressing cells revealed the role of miRs in murine NK cells and ILC1s (223).…”
Section: Epigenetic and Microrna-mediated Regulation Of Nk Cell And Imentioning
confidence: 99%
“…Available data implicate small non-coding RNA molecules ( 221 226 ), such as microRNAs (miRs), to regulate posttranscriptional gene expression by binding to the 3′ untranslated region (UTR) of mRNAs and inducing either suppression or mRNA translation or its degradation ( 227 ). Deletion of the RNase III enzyme Dicer-1, an enzyme required for the generation of single-stranded 20–25 bp long non-coding RNA molecules, in NKp46-expressing cells revealed the role of miRs in murine NK cells and ILC1s ( 223 ). The number of NK1.1 + cells in the organs of Dicer-1 mutant mice was affected, along with the impaired maturation of NK cells.…”
Section: Epigenetic and Microrna-mediated Regulation Of Nk Cell And Imentioning
confidence: 99%
“…Recent studies have shown that miRs are also important for NK cell development and function. Using a Dicer1-deficient mouse model that abrogates miR biogenesis in NK cells, Degouve et al ( 72 ). showed that a 10-fold global reduction in miR expression resulted in reduced NK cell numbers, aberrant NK cell maturation, along with attenuated IFN-γ production and cytotoxicity against target cells.…”
Section: Posttranscriptional Regulation Of Nk Cell Development By Micmentioning
confidence: 99%
“…showed that a 10-fold global reduction in miR expression resulted in reduced NK cell numbers, aberrant NK cell maturation, along with attenuated IFN-γ production and cytotoxicity against target cells. Given that IL-15 signaling via the STAT5 and mTOR pathways was significantly affected, it was proposed that miRs regulate NK cell survival by modulating IL-15 sensitivity ( 72 ). Although it remains unclear as to whether NK cell survival is dependent on specific miRs, miR-155 and miR-15/16 are unlikely candidates since mice that are deficient for either miR have normal NK cell numbers ( 73 , 74 ).…”
Section: Posttranscriptional Regulation Of Nk Cell Development By Micmentioning
confidence: 99%
“…The precise interplay between cytokines, mTOR and T‐box factors in NK cells remains however to be fully elucidated. Subtle variations in T‐bet/Eomes ratios may also implicate microRNAs that have a strong impact on NK cell maturation .…”
Section: Introductionmentioning
confidence: 99%